'Fatal 2, 4-dinitrophenol poisoning… coming to a hospital near you'. Issue 8 (29th May 2010) - Siegmueller, Claas; Narasimhaiah, Raghunanda
Abstract : An adult man was brought into the emergency department after deliberate ingestion of dinitrophenol: an agent that uncouples mitochondrial oxidative phosphorylation. The patient rapidly developed a hyper-metabolic state with fever, respiratory failure and died within a few hours after admission. Dinitrophenol is used in the manufacture of dyes, pesticides and explosives. Sub-acute poisoning is associated with weight-loss and the substance had been prescribed for this purpose during the 1930s in the United States before being banned due to serious side effects. Although remaining unlicensed as a drug, dinitrophenol is widely available through mail-order websites and online pharmacies, which promote it as an anti-obesity treatment. This case highlights the need for awareness of possibly increasing rates of accidental poisoning with a growing obesity prevalence and availability of this unlicensed drug through the internet. Additionally, we discuss the use of dantrolene in dinitrophenol poisoning and question whether current Toxbase/UK National Poison Information Service treatment guidelines regarding the indication and dosing of this drug, the only relatively specific treatment in dinitrophenol poisoning presently recommended, could be revised.